Enhancing the intermolecular singlet fission efficiency by controlling the self-assembly of amphipathic tetracene derivatives in aqueous solution. Issue 36 (6th September 2019) - Tang, Zhaofeng; Zhou, Sainan; Wang, Xiangyang; Liu, Heyuan; Yan, Xinyu; Liu, Shanshan; Lu, Xiaoqing; Li, Xiyou
Abstract : Introduction of the carboxyl group onto tetracene can change the singlet fission mechanism and increase the singlet fission yield in its nanoparticles. Abstract : Two kinds of nanoparticles of two tetracene derivatives with (PhTc-COOH) or without (PhTc) carboxylic groups are prepared with the re-precipitation method. Scanning electron microscopy and dynamic light scattering experiments reveal different morphologies and sizes of these two kinds of nanoparticles. Furthermore, a stronger intermolecular interaction is achieved in PhTc-COOH nanoparticles than in PhTc nanoparticles as revealed by their steady-state absorption spectra. This is most likely due to the more parallel and closer arrangement of the tetracene molecules in PhTc-COOH nanoparticles driven by the hydrophilic effect of the carboxyl group. Time-resolved fluorescence and ultrafast transient absorption spectra reveal that both PhTc-COOH and PhTc nanoparticles can conduct singlet fission (SF) upon photoexcitation. However, the SF in PhTc-COOH nanoparticles is much faster and more efficient than in PhTc nanoparticles. More importantly, SF mechanisms in these two nanoparticles are different. A charge-transfer (CT) state is identified as an intermediate for the SF in PhTc nanoparticles, while no CT state is detected in the SF process of PhTc-COOH nanoparticles. This work suggests that introduction of supramolecular interaction to tune the arrangement of tetracene molecules in nanoparticles is a useful strategy towards efficient SF. This conclusion might be also applied in other SF molecular systems.